2016
DOI: 10.1039/c5ta07780j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-based nanomaterials for efficient photoenergy conversion

Abstract: Graphene oxide nanomaterials with tunable electronic properties act as efficient photoenergy-conversion media in photoluminescence, photovoltaics, and photocatalytic water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 228 publications
1
37
0
Order By: Relevance
“…A perovskite precursor solution was spin-coated in the glove box. The (FAPbI 3 [21,22] This composition contains a lead excess as reported previously. The solution was spin-coated at 1000 rpm for 10 s and continuously at 6000 rpm for 30 s. During the second step, when approximately 15 s left before finish, 100 mL of anhydrous chlorobenzene was added.…”
Section: Device Fabricationmentioning
confidence: 73%
See 1 more Smart Citation
“…A perovskite precursor solution was spin-coated in the glove box. The (FAPbI 3 [21,22] This composition contains a lead excess as reported previously. The solution was spin-coated at 1000 rpm for 10 s and continuously at 6000 rpm for 30 s. During the second step, when approximately 15 s left before finish, 100 mL of anhydrous chlorobenzene was added.…”
Section: Device Fabricationmentioning
confidence: 73%
“…[2][3][4][5] The development of solution-processable graphene, such as the chemical exfoliation of graphite into graphene oxide, allowed the functionalization and processing of graphene, extending its use in the different layers of solutionprocessable solar cells. [6,7] Among different solar cell technologies, organic-inorganic hybrid perovskite solar cells (PSCs) have been dominating the interest of the scientific research community for their impressive technological development with power conversion efficiency (PCE) values beyond 22 % in a short of six years of research.…”
mentioning
confidence: 99%
“…So it is important to modify the GO sheets with both p‐ and n‐type conductivities that may produce a photocatalytic medium effective for overall water splitting into H 2 and O 2 . Based on the structural characteristics required for photocatalytic water‐splitting, Teng et al synthesized N‐doped GO‐QDs as the catalyst . The electrochemical Mott−Schottky analysis results indicated that the obtained N‐doped GO‐QDs exhibited both p‐ and n‐type conductivities, in which the n‐conductivity was caused by embedding N atoms in the graphene frame, and the p‐conductivity by grafting oxygen functionalities on the graphene surface.…”
Section: N‐doped Graphenementioning
confidence: 99%
“…The heteroatom doping approach of introducing impurities into a matrix of nanocarbon materials, through surface transfer doping and substitutional doping, presents an avenue to efficiently enhancep hotocatalytic properties of carbonaceousm aterials through the improvedo ptical and electrochemical properties, structurala nd textural characteristics,t he adsorptive and mass transfer behavior,a nd the properties of active sites. [1,4,[7][8][9][10][77][78][79][80][81][82][83][84] As ac onsequence, the doping of photocatalysts garnerscontinually growing interest. By searching "photocatalysis" and then refining by "doping" (SciFinder,o nA pril 20, 2017),2 0799 publications can be obtained.I ndicated in Figure2is the explosive growth of doping of photocatalysts in the last ten years.…”
Section: Introductionmentioning
confidence: 99%
“…By searching "photocatalysis" and then refining by "doping" (SciFinder,o nA pril 20, 2017),2 0799 publications can be obtained.I ndicated in Figure2is the explosive growth of doping of photocatalysts in the last ten years. Indeed, the doping by heteroatoms has attracted great interest in fabricating advanced photocatalysts including both non-metallic photocatalysts, [1,4,[7][8][9][10][77][78][79][80][81][82][83][84] and metallicp hotocatalysts. [84][85][86][87][88][89][90][91][92][93][94][95] In this Review,w ef ocus on the non-metallic heteroatoms-doped carbonaceous photocatalysts for energy conversion and environmental remediation applications.…”
Section: Introductionmentioning
confidence: 99%